Menguasai Literasi Teknologi untuk Mengatasi Risiko Keamanan Cyber - Repi, Predi Ari; Nasution, Muhammad Irwan Padli (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The growing reliance on digital technology has produced new concerns for cyber security. Technological literacy has been identified as a significant factor in reducing the hazards linked with the usage of technology. This article examines the need of technological literacy in tackling cyber security issues, as well as integrative approaches that incorporate education and digital awareness. This article identifies methodologies and best practices for generating technical literature for cyber-security reasons using a literature review and critical analysis. Practical advice are also provided to improve educational efforts and digital awareness in mitigating cybersecurity risks in a variety of settings.